Association between urinary angiotensinogen, hypertension and proteinuria in pregnant women with preeclampsia. (September 2015) - Yilmaz, Z; Yildirim, T; Yilmaz, R; Aybal-Kutlugun, A; Altun, B; Kucukozkan, T; Erdem, Y
Introduction: Preeclampsia is a life-threatening disorder of pregnancy. The pathogenic mechanisms of preeclampsia remain uncertain. The aim of this study is to investigate the relation between urinary angiotensinogen (UAGT) levels, an indicator of local renin–angiotensin system (RAS) activity in the kidney, and blood pressure and urinary protein excretion in preeclampsia. Materials and methods: For this study, 90 women aged between 20–39 years were recruited. Spot urine samples were collected to measure urinary angiotensinogen/creatinine ratio (UAGT/UCre). Log(UAGT/UCre) was compared in pregnancies with and without preeclampsia and non-pregnant controls. Factors affecting log(UAGT/UCre) in pregnancies were also investigated. Results: In all pregnancies log(UAGT/UCre) levels were significantly higher than in non-pregnant controls (0.58±0.19 vs. 0.33±0.14, respectively, p =0.002). However, log(UAGT/UCre) levels in pregnancies with preeclampsia were slightly lower than in normal pregnancies (0.52±0.18 vs. 0.64±0.19, respectively, p =0.012). Log(UAGT/UCre) levels were correlated positively with blood pressure and proteinuria in pregnancies with preeclampsia. However, log(UAGT/UCre) levels were not correlated with age, height, body weight, gestational age, body mass index, and serum creatinine. Conclusion: This study showed that elevated local RAS activity in kidney was correlated with high blood pressure and proteinuria in preeclampsia. Local RAS activation in the kidneys may be one of the contributing factors in the development of preeclampsia.